Effect of nitrate treatment on functional capacity and exercise time in patients with heart failure: a systematic review and meta-analysis. Issue 8 (August 2020) - Long, Wenjie; Liao, Huili; Liu, Qingqing; Ning, Yile; Wu, Tingchun; Kang, Jinhua; Liu, Jianhong; Xian, Shaoxiang; Yang, Zhongqi
Objectives: Heart failure (HF) is a common and potentially fatal condition. In 2015, HF affected approximately 40 million people globally. Evidence showing that the use of nitrates can improve clinical outcomes in patients with HF is limited. This study aimed to assess the effect of nitrates on functional capacity and exercise time in patients with HF. Methods: PubMed, Cochrane Library, and Embase databases were reviewed for articles on the use of nitrates and other treatments for patients with HF. The primary endpoints were the 6-minute walk test distance, exercise time, and quality of life. Secondary endpoints were all-cause mortality, arrhythmia, hospitalization, and worsening HF. The weighted mean difference, risk ratio, and 95% confidence interval were calculated. Results: A total of 14 related studies that comprised 26, 321 patients were included. No significant differences were found in the 6-minute walk test distance, exercise time, and quality of life between the nitrate and control treatment groups. There were also no differences in all-cause mortality, the incidence of arrhythmia, hospitalization, and worsening HF between these two groups. Conclusion: Patients with HF who receive nitrate treatment do not have better quality of life or exercise capacity compared with controls.